Pengaruh Stock Split Terhadap Volume Perdagangan Dan Spread Bid-Ask: Bukti Dari Pasar Saham Indonesia Pada Tahun 2022 - Rahmat Fajar Santoso Muslim; Maya Sari; Imas Purnamasari (Jurnal Pendidikan Akuntansi & Keuangan, 2023)
This study aims to examine the impact of stock splits on trading volume and bid-ask spread in the Indonesian stock market. The research employs a quantitative approach with a pre-post design, comparing the data before and after the stock splits. The data used in the analysis were obtained from the Indonesia Stock Exchange (IDX) and include information on the trading volume and bid-ask spread for 11 companies that underwent stock splits. The analysis compares the average trading volume and bid-ask spread before and after the announcement of stock splits. The findings indicate that stock splits have an influence on trading volume and bid-ask spread in the Indonesian stock market in 2022. However, the impact is not significant for all companies and can be influenced by other factors such as market conditions, investor sentiment, company performance, and overall market liquidity.